2015
DOI: 10.1038/srep16632
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Macrophage Functional Polarity towards Anti-Inflammatory Phenotype with Plasmid DNA Delivery in CD44 Targeting Hyaluronic Acid Nanoparticles

Abstract: The purpose of this study was to modulate macrophage polarity from the pro-inflammatory M1 to anti-inflammatory M2 phenotype using plasmid DNA (pDNA) expressing interleukin-4 (IL4) or interleukin-10 (IL10)-encapsulated in hyaluronic acid-poly(ethyleneimine) (HA-PEI) nanoparticles (NPs). The HA-PEI/pDNA NPs with spherical shape, average size of 186 nm were efficiently internalized by J774A.1 macrophages. Transfection of HA-PEI/pDNA-IL4 and HA-PEI/pDNA-IL10 NPs increased IL4 and IL10 gene expression in J774 macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 38 publications
2
106
0
Order By: Relevance
“…Macrophages/monocytes are key players in the modulation of immunological responses and inflammation [40,41]. The M1 or M2 macrophage phenotype is important for promoting inflammation or healing, respectively [6].…”
Section: Fasudil Carried Liposomes Polarized Macrophages/monocytes Frmentioning
confidence: 99%
“…Macrophages/monocytes are key players in the modulation of immunological responses and inflammation [40,41]. The M1 or M2 macrophage phenotype is important for promoting inflammation or healing, respectively [6].…”
Section: Fasudil Carried Liposomes Polarized Macrophages/monocytes Frmentioning
confidence: 99%
“…In vivo models of C57BL/6 mice intraperitoneally injected with LPS and IFN-γ presented notably down-regulated expression of iNOS (from 255-fold to about five-fold relative to the LPS-treated control) level and up-regulated expression of CD163 level following treatment with HA-PEI/pDNA NPs [46]. Further study suggested that targeting CD44-overexpressed peritoneal macrophages by HA and the capacity of PEI for encapsulating nucleic acids made HA-PEI easily internalized by the macrophage.…”
Section: Nps Modulate Macrophage Polarization and Reprogrammingmentioning
confidence: 99%
“…Moreover, previous reports have shown that HA can be easily cleared from the body through different excretion processes with a total turnover of about 5 g of HA per day in humans . HA‐based NPs also hold great potential for the specific targeting of inflammatory macrophages during sustained inflammation because of the specific interaction between HA and membrane receptors such as CD44, which are highly expressed on macrophages . Upon the formation of the hydrogels containing miR‐223* loaded HA NPs, we optimized the mechanical, physical, and adhesive properties of the hydrogels to ensure that they can adhere to the native skin and cover the wound during the healing process.…”
Section: Introductionmentioning
confidence: 99%